A DNA Barcoding Multilocus Analysis in the Cucurbitaceae Family - Nurbaiti, Nurbaiti; Roslim, Dewi; Herman, Herman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Cucurbitaceae family is a very diverse family of angiosperms and is often used as a traditional medicine because it produces secondary metabolites in the form of Cucurbitacin B, D, E, and I. The identification and determination of filogeny between species in the Cucurbitaceae family using a single DNA barcode locus is still inefficient. The purpose of this study is to analyze the appropriate and effective combination of DNA barcode multiloci for species identification from the Cucurbitaceae family. The materials used in this study are the database ofns matK, rbcL, ITS and trnL-F IGS from the Cucurbitaceae Family and the outgroup, namely Tetrameles nudiflora which was explored from Genbank through the NCBI website, and then performed MSA (Multiple Sequence Alignment) using MAFFT v.7 software. and sequence editing using Bioedit v.7.2. then DNA sequence analysis and phylogenetic tree construction using MEGA 11. The results show that the ITS locus is the most efficient barcode to identify and distinguish species in the Cucurbitaceae family. The combination of multiloci of the ITS, matk, and trnL-trnF IGS also has the potential to identify and differentiate species in the Cucurbitaceae family on the condition that ITS must be included (be the main locus) and not include rbcL because of its low variability.